2021
DOI: 10.5614/jpwk.2021.32.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Urban Sustainability and Resilience Governance: Review from The Perspective of Climate Change Adaptation And Disaster Risk Reduction

Abstract: The imperative of ‘making cities resilient and sustainable’ necessitates cities to develop adaptation concepts and practices in response to the uncertainty, rapid change, and complexity of urban areas. A new concept of governance that can answer the challenges of contemporary urban development and ensure long-term sustainable development is required. This study aimed to identify the general framework of adaptive urban governance by review, elaboration, and analysis of documents, in this case, scientific articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
(111 reference statements)
0
13
0
Order By: Relevance
“…Urban governance plays a critical role in building resilient communities, with adaptive and anticipatory governance strategies being vital when integrating disaster risk reduction (DRR) and climate change adaptation (CCA) (UNDP, 2017). Addressing real-world challenges like DRR and CCA integration requires alternative perspectives, research, consensus, and multidisciplinary collaboration (Begum et al, 2014a;Ni'mah et al, 2021;Valente et al, 2022).…”
Section: Discussion: Converging Drr and Cca In Malaysiamentioning
confidence: 99%
See 1 more Smart Citation
“…Urban governance plays a critical role in building resilient communities, with adaptive and anticipatory governance strategies being vital when integrating disaster risk reduction (DRR) and climate change adaptation (CCA) (UNDP, 2017). Addressing real-world challenges like DRR and CCA integration requires alternative perspectives, research, consensus, and multidisciplinary collaboration (Begum et al, 2014a;Ni'mah et al, 2021;Valente et al, 2022).…”
Section: Discussion: Converging Drr and Cca In Malaysiamentioning
confidence: 99%
“…Sustainability in implementing DRR with CCA is the research focus. This involves organizational capacity building, efficient funding, education, stakeholder networks, and more (Pereira et al, 2010;Shaw et al, 2010;Forino et al, 2015b;Serrao-Neumann et al, 2015;Ni'mah et al, 2021). Efforts to incorporate DRR and CCA aim for sustainability at various administrative levels.…”
Section: Discussion: Converging Drr and Cca In Malaysiamentioning
confidence: 99%
“…However, the common visions established in the first workshops, as well as the backcasting scenario exercises, certainly showed that stakeholders possess a high capacity to envision common goals and objectives for the future of the lakes, and that they are willing to shape the future using anticipatory measures, despite coming from diverse sectors, backgrounds and having different personal objectives. The expression of such foresight capacity corresponds with the motivation behind the adhesion to anticipatory governance principles (Boyd et al, 2015;Ni'mah et al, 2021). Yet, making use of the stakeholders' common visions and of the backcasting scenarios they created is the critical step that they still need to take to integrate foresight into local SES governance.…”
Section: Foresightmentioning
confidence: 99%
“…In related perspectives, the concern to connect urban policies with sustainability has become a multidisciplinary theme overcoming the barriers of traditional urban planning, promoted directly by architects and indirectly by the agents producing the space (Bernardi, 2009; Corrêa, 1989). In fact, urban sustainability has become a goal for several nations, in the search to propose and enable cities that meet the needs of its users (Ni'mah et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%